Fluid simulations of plasma filaments in stellarator geometries with BSTING. (6th December 2018) - Shanahan, B; Dudson, B; Hill, P
Abstract: Here we present first results simulating plasma filaments in non-axisymmetric geometries, using a fluid turbulence extension of theBOUT++ framework. This is made possible by the implementation of the flux coordinate independent (FCI) scheme for parallel derivatives, an extension of the metric tensor components which allows them to vary in three dimensions, and development of grid generation. Tests have been performed to confirm that the extension to three dimensional metric tensors does not compromise the accuracy and stability of the associated numerical operators. Recent changes to the FCI grid generator inBOUT++, including a curvilinear grid system which allows for potentially more efficient computation, are also presented. Initial simulations of seeded plasma filaments in a non-axisymmetric geometry are reported. We characterize filaments propagating in the closed-field-line region of a low-field-period, rotating ellipse equilibrium as inertially-limited by examining the velocity scaling and currents associated with the filament propagation. Finally, it is shown that filaments in a non-axisymmetric rotating ellipse equilibrium propagate in a toroidally nonuniform fashion, and it is determined that the long connection lengths in the scrape-off-layer enable parallel gradients to establish, which has consequences for interpretation of experimental data.